Antimalarial compounds exhibit variant- and cell-type-specific activity against SARS-CoV-2 isolated in Panama - Quijada, Mario; Castillo-Bultron, Marlene; Díaz, Yamilka; Pitti, Yaneth; Franco, Danilo; De La Guardia, Carolina; Campos, Dalkiria; Cornejo, Eduardo; Núñez, Marlon; Mendoza, Lariza; López-Vergès, Sandra; Magallon-Tejada, Ariel H.; et al. (Frontiers in Pharmacology, 2025)
BackgroundThis study evaluates the antiviral activity of antimalarial compounds against SARS-CoV-2 variants isolated in Panama (2020–2022).MethodsFor this purpose, we conducted a series of in vitro assays in two host mammalian cell systems, Vero-E6 and Calu-3 cells, to assess the antiviral activity of twenty-six antimalarials and antiviral compounds against the Delta and A2.5 variants.ResultsIn the initial screening using Vero-E6 cells, with an antiviral inhibition threshold of ≥20% and cell viability of ≥80%, chloroquine (CQ) significantly inhibited the Delta variant. Meanwhile, amodiaquine (AQ), artemisone (ASO), and ivermectin (IVM) showed activity against the A2.5 variant. In Calu-3 cells, a wider variety of compounds, including chloroquine (CQ), amodiaquine (AQ), artesunate (AS), lumefantrine (LUM), and hydroxychloroquine (HCQ), were found to be effective against the Delta variant. However, only amodiaquine (AQ) and arteether (AE) showed activity against the A2.5 variant, indicating that the response varies depending on the variant and the type of cells involved. Secondary screenings further demonstrated CQ’s high inhibitory activity, with an IC50 of 6.3 μM and a selectivity index of 8, followed by HCQ, which was 1.8 times more potent against A2.5 than Delta. Time-of-addition experiments suggested that CQ and primaquine (PQ) were ineffective during the viral adsorption phase but showed a dose-dependent antiviral effect against the A2.5 variant in the early replication phase, whereas the Delta variant showed resistance.ConclusionThis study underscores the critical role of selecting appropriate cell models for SARS-CoV-2 research, as drug efficacy varies between viral variants and host cell types.